Behaviour of high-strength concrete under biaxial loading conditions - Hussein, Amgad Ahmed (1998)
Thesis (Ph.D.)--Memorial University of Newfoundland, 1998. Engineering and Applied Science Bibliography: leaves 229-245. With the increasing applications of high strength concrete in the construction industry, the understanding of its behaviour under multiaxial loading is essential for reliable analysis and safe design. This thesis encompasses an investigation of the behaviour of high strength concrete under biaxial loading conditions, and a constitutive modelling study to enable numerical prediction, through the finite element method, of such a behaviour. -- The experimental phase included the evaluation and design of the loading platens. The test set-up and supports are very crucial to this type of testing due to the friction that exists between the testing platens and the specimen. A theoretical study using the finite element approach was conducted to investigate the effect of confinement on the displacement field in addition to the stress distribution in the loading direction. Three types of loading platens were examined: the dry solid platens, the brush support and teflon friction reducing pads. The results of the simulation indicated that the most homogeneous stress and displacement field are achieved through the brush platens. Based on the finite element investigation, the size and dimensions of the brush platens were recommended. They were used in the experimental study. -- A test set-up was designed and manufactured. Modern control schemes and highspeed data acquisition system were be used to monitor the material response and collect the experimental results. Four different types of high strength concrete plate specimens were tested under different biaxial load combinations. The principal deformations in the specimen were recorded and the crack patterns and failure modes were examined. Based on the strength data, failure envelopes were developed for each type of concrete. The test results revealed that the failure envelopes of concrete depends on the concrete strength and on the type of aggregates. A pronounced difference was found between the high strength light weight and the high strength normal weight concrete. The deformation characteristics indicated that high strength concrete shows a linear behaviour up to a higher stress than normal strength concrete. It also has a higher discontinuity limits. The observed failure modes showed that there is no fundamental difference in the crack patterns and failure modes due to the increase in the compressive strength of the concrete or due to the use of light weight aggregates under different biaxial loading combinations. -- The test results were used to modify and calibrate a fracture energy-based non-associated model for high-strength concrete. The model was implemented in a general purpose finite element program and was verified against the test results. Using the proposed constitutive model, a finite element study was carried out to analyze the standard compression test on a concrete cylinder. The effects of the compressive strength, cylinder size, loading platens and sulphur capping were investigated. The study confirmed that a triaxial compressive stress state exists at the cylinder end, and a large stress concentration occurs at the corner. The simulation results revealed that the use of a standard bearing block is essential in testing high strength concrete. Moreover, in some cases, the use of a non standard bearing block can result in a lower strength, which was observed experimentally. The simulation provided an explanation for such a behaviour. Finally, the finite element analysis demonstrated that the use of soft materials, as friction reducers, could create drastic changes in the state of stress in the specimen as well as its compressive strength. The use of soft materials should, therefore, be carried out with caution.